2022
DOI: 10.3390/cancers14071810
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer: The Contribution of CXCL12 and Its Receptors CXCR4 and CXCR7

Abstract: Colorectal cancer is one of the most common cancers, and diagnosis at late metastatic stages is the main cause of death related to this cancer. This progression to metastasis is complex and involves different molecules such as the chemokine CXCL12 and its two receptors CXCR4 and CXCR7. The high expression of receptors in CRC is often associated with a poor prognosis and aggressiveness of the tumor. The interaction of CXCL12 and its receptors activates signaling pathways that induce chemotaxis, proliferation, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 277 publications
(384 reference statements)
0
13
0
1
Order By: Relevance
“…It has been suggested that E6/E7 might exhibit crosstalk with these signaling pathways, affecting cell adhesion and limiting the immune response. CXCR4 ( Zou et al, 1998 ; Goïta and Guenot, 2022 ) is a chemokine G protein-coupled transmembrane receptor released by stromal cells. Stromal cell-derived factor-1 (SDF-1; CXCL12), a ligand of CXCR4, induces B-cell proliferation and T-cell recruitment by activating CXCR4-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that E6/E7 might exhibit crosstalk with these signaling pathways, affecting cell adhesion and limiting the immune response. CXCR4 ( Zou et al, 1998 ; Goïta and Guenot, 2022 ) is a chemokine G protein-coupled transmembrane receptor released by stromal cells. Stromal cell-derived factor-1 (SDF-1; CXCL12), a ligand of CXCR4, induces B-cell proliferation and T-cell recruitment by activating CXCR4-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that the signaling triggered by factors that mediate the communication between TME and CRC cells is of great importance. Since Wnt/β-catenin is involved in most of the processes related to CRC genesis and progression[ 8 , 47 ], in this section we focus on the factors from the TME able to modulate this pathway. Figure 3 schematizes the complex interrelationships between the TME and CRC cells that lead to the activation of β-catenin and the consequent effects on disease progression.…”
Section: Tme Factors and Conditions That Modulate The Wnt/β-catenin P...mentioning
confidence: 99%
“…In oxaliplatin-resistant human CRC cells, the upregulation of CXCR4 has a critical role in the development of oxaliplatin-resistant characteristics [ 14 ]. The CXCR4-mediated signaling might have a specific role in regulating drug resistance mechanisms in CRC [ 15 ]. As a growing number of studies have demonstrated that the expression level of CXCR4 in CRC may influence the sensitivity of CRC to chemotherapeutic drugs such as oxaliplatin, the expression of CXCR4 in drug-resistant CRC cell lines for cancer chemotherapy has still been further elucidated.…”
Section: Introductionmentioning
confidence: 99%